The Role of Postoperative Radiation and Chemoradiation in Merkel Cell Carcinoma: A Systematic Review of the Literature - Hasan, Shaakir; Liu, Liyu; Triplet, Jacob; Mansur, David (Frontiers in Oncology, 2013)
Objective: A systematic review of the literature was undertaken to investigate whether adjuvant radiotherapy and/or chemotherapeutics offered any additional benefit than surgery alone in the treatment of Merkel Cell Carcinoma (MCC). Methods: A PubMed, MEDLINE search was conducted between 1995 and 2013, to identify reported cases of surgically treated MCC followed by either observation, radiation, or chemoradiation. Patient demographics and outcomes were recorded and compared in a systematic fashion. Results: Thirty-four studies (n = 4475) were included. The median age was 73 years, median follow up was 36 months and there was a 1.5:1 ratio of men to women. All 4475 patients had surgery, 1975 had no further treatment, 1689 received postoperative RT, and 301 received postoperative chemoRT. The most common site was face/head/neck, 47.8%. Stage 1 was the most common clinical stage at diagnosis (57%). Three-year local control was 20% (median 10%) in the observation cohort, compared to 65% (62%) with postoperative RT, and 67% (75%) with postoperative chemoRT; these findings were statistically significant (P < 0.001). Recurrence was found to be 38% (60%) in the observation cohort, compared to 23% (20%) with postoperative RT (P < 0.001). Three-year overall survival (OS) was found to be 56% (57%) in the observation cohort, compared to 70% (78%) with postoperative RT and 73% (76%) with postoperative chemoRT (P < 0.001). The observation cohort had a median OS of 44 months compared with 64 months (P < 0.001) in the postoperative RT cohort. There was no statistically significant difference in any parameters assessed between postoperative radiation and postoperative chemoradiation arms. Conclusion: The comprehensive collection of retrospective data suggests a survival and control benefit for postoperative radiation in MCC. No differences were noted between adjuvant radiation and chemoradiation. This analysis indicates the need for prospective trials with patients stratified by known prognostic factors.